The Effect of Business Location and Marketing Strategy on The Success of Barbershop Business in Male Zone Jl. SM Raja Simpang Mangga - Randi Syahputra Ritonga; M. Rusdi; Nurhabibah Ritonga (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the effect of business location, marketing strategy, on business success. The object of this study is Barbershop in Male Zone jl. SM Raja Simpang Mangga. The sampling technique uses nonprobality sample. Data collection techniques use questionnaires and documentation and data analysis tools use multiple linear regression analysis. The data analysis technique used is the f test and t test at a significance level of alpha 0.05. The hypothesis test shows the results of the influence of business capital on business success with a t value of 5.431 at a significance level of 1.672, the influence of entrepreneurial ability on business success with a t value of 8.004 at a significance level of 1.672. Thus, the hypothesis in this study shows that business location and marketing strategy simultaneously have a significant effect on the success of the Barbershop business in Male Zone jl. SM Raja Simpang Mangga, entrepreneurial ability has a partial positive and significant effect on the success of the Barbershop business in Male Zone jl. SM Raja Simpang Mangga.